(untitled) (Bangladesh Journal of Botany, 2024)
This study investigates the allelopathic effects of Parthenium hysterophorus L. leaf and root extracts on the germination and growth of three rice varieties (Hira dhan, BRRI dhan-28, and BRRI dhan-29) in Bangladesh. Leaf and root extracts of P. hysterophorus were prepared at different concentrations and applied to rice seeds in a controlled environment. Results showed that low concentrations of the extracts inhibited seed germination and growth, with significant differences among rice varieties (p < 0.05). Hira dhan exhibited the most sensitivity, with germination rates as low as 42.86% under high extract concentrations. In contrast, BRRI dhan-29 showed a stimulatory effect, particularly at low concentrations. The shoot and root lengths of Hira dhan and BRRI dhan-29 were significantly inhibited at higher concentrations, while BRRI dhan-28 demonstrated growth stimulation. The fresh and dry weights of roots and shoots varied significantly among the varieties with the greatest inhibitory effect observed in BRRI dhan-29. These findings align with previous studies, suggesting that allelochemicals in P. hysterophorus, such as parthenin and phenolic acids, play a critical role in inhibiting rice growth. The study emphasizes the need for further research on allelopathic interactions and suggests that controlling P. hysterophorus at the crop emergence stage could mitigate its suppressive effects on rice growth. Bangladesh J. Bot. 53(3): 411-421, 2024 (September)